An Analysis of Population Productivity and Its Relationship with the Regional Economic Structure in Tolitoli Regency - M. Nure, Hedrat; Saputra, Andhy; Fathur, Alfansyah; Salfiah, Elfirah (STIE Mujahidin Tolitoli Development Economics Study Program, 2025)
This study aims to analyze the relationship between population productivity and the regional economic structure in Tolitoli Regency. The data used is sourced from the official publication of the Central Bureau of Statistics through the Tolitoli in Figures 2024 document. The results show that the agriculture, forestry, and fisheries sectors are the largest contributors to labor absorption but do not provide a proportional contribution to the Gross Regional Domestic Product (GRDP). This imbalance indicates low productivity in labor-intensive sectors and highlights the need for economic transformation toward higher value-added sectors. The study recommends strengthening policies that support economic diversification, improving human resource quality, and developing new productive sectors as strategies to enhance regional productivity and competitiveness. These findings are expected to serve as a foundation for formulating a more inclusive and sustainable regional economic development strategy.